Gestational Outcome in Thrombophilic Women with Recurrent Pregnancy Loss Treated by Enoxaparin - Brenner, B.; Hoffman, R.; Blumenfeld, Z.; Weiner, Z.; Younis, J. S. (Thrombosis and Haemostasis, 2000)
Inherited and acquired thrombophilia are associated with recurrent pregnancy loss (RPL). We have evaluated the efficacy and safety of the low molecular weight heparin enoxaparin in 50 women, (mean age 26 ± 3 years) with RPL (>3 losses in 1st, >2 losses in 2nd and >1 loss in 3rd trimester) who were found to harbor thrombophilia. Twentyseven had a solitary thrombophilic defect, and twenty-three women had combined thrombophilic defects: 17 – two defects and 6 – three defects. Following diagnosis of thrombophilia, sixty-one subsequent pregnancies were treated with the low molecular weight heparin enoxaparin throughout gestation until 4 weeks after delivery. Dosage was 40 mg/day in women with solitary defect and 80 mg/day in combined defects. Aspirin, 75 mg daily was given in addition to enoxaparin to women with antiphospholipid syndrome. Forty-six out of 61 (75%) gestations treated by enoxaparin resulted in live birth compared to only 38/193 (20%) of the untreated pregnancies in these 50 women prior to diagnosis of thrombophilia (p <0.00001). In 23 women without a single living child following 82 untreated gestations, antithrombotic therapy resulted in 26/31 (84%) successful deliveries (p <0.0001). In 20 women with a prior living child, antithrombotic therapy improved successful delivery from 33/86 (38%) to 20/21 (95%) (p <0.0001). Enoxaparin dose of 40 mg/day resulted in live birth in 24/35 (69%) of gestations, compared to 19/23 (83%) gestations in women treated with 80 mg/day (p = 0.37). Only one thrombotic episode and one mildbleeding episode were noticed during enoxaparin therapy. Enoxaparin is safe and effective in prevention of pregnancy loss in women with inherited and acquired thrombophilia.
Keywords: Pregnancy; thrombophilia; factor V Leiden; low molecular weight heparin